2006
DOI: 10.1093/annonc/mdj096
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative systemic (neo-adjuvant) therapy with trastuzumab and docetaxel for HER2-overexpressing stage II or III breast cancer: results of a multicenter phase II trial

Abstract: PST with trastuzumab plus docetaxel achieved promising efficacy, with a high pCR rate and good tolerability, in women with stage II or III HER2-positive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
44
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 17 publications
10
44
1
1
Order By: Relevance
“…This treatment strategy is associated with a high pathologic response rate (Coudert et al, 2005), which is in accordance with the good efficacy previously reported for the combination of paclitaxel and trastuzumab in this setting (Bines et al, 2003;Burstein et al, 2003;Schiffhauer et al, 2003;Van Pelt et al, 2003;Baselga et al, 2004). In order to discount the effects of intratumoural immune cell modifications that may be induced by conventional chemotherapy drugs, the control group comprised tumours from patients treated with two different PST (Clynes et al, 2000).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This treatment strategy is associated with a high pathologic response rate (Coudert et al, 2005), which is in accordance with the good efficacy previously reported for the combination of paclitaxel and trastuzumab in this setting (Bines et al, 2003;Burstein et al, 2003;Schiffhauer et al, 2003;Van Pelt et al, 2003;Baselga et al, 2004). In order to discount the effects of intratumoural immune cell modifications that may be induced by conventional chemotherapy drugs, the control group comprised tumours from patients treated with two different PST (Clynes et al, 2000).…”
Section: Discussionsupporting
confidence: 69%
“…These findings may partially explain the synergistic activity of trastuzumab and docetaxel in the treatment of HER2-positive breast cancer and the excellent clinical outcomes afforded by this combination. In the TAXHER01 study (Coudert et al, 2005), tumours that were centrally confirmed to be HER2 positive displayed a pCR of 54%. This is superior to that observed with non-trastuzumab-containing neoadjuvant regimens in unselected patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoadjuvant trastuzumab plus chemotherapy demonstrated a significant increase in pCR rates (15.7% vs. 31.7%; P < 0.001). pCR rates with neoadjuvant trastuzumab and anthracycline-free regimens in other studies range from 11% to 76% 22,24,25,[30][31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…serving surgery or in vivo assessment of tumor response. The addition of trastuzumab to neoadjuvant chemotherapy has shown to significantly increase pCR (pathological Complete Remission), breast sparing surgery and event-free survival in women with operable, HER2-positive disease [17,18]. The phase III randomized study NeoALTTO [19] (Neoadjuvant Lapatinib and/or Trastuzumab Treatment Optimization) was designed to compare the efficacy of neoadjuvant lapatinib, trastuzumab or their combination, in association with paclitaxel.…”
Section: Lapatinib In Combination With Endocrine Agentsmentioning
confidence: 99%